The Role of Competitive Advantage as Mediating The Effect of Strategic Planning on Company Performance - Gatot Soebroto; Budiyanto Budiyanto (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: The purposes of this research are to determine the role of competitive advantage as mediating the effect of strategic planning on company performance. Design/methodology/approach: The steps are first, determine the influence of strategic planning on competitive advantages; second, determine the influence of competitive advantages on company performance, third determine the role of competitive advantages as a mediating variable from the influence of strategic planning on company performance. Findings: The results showed that strategic planning has a positive and significant effect on competitive advantages and organizational performance. Competitive advantage has a positive and significant effect on organizational performance. Competitive advantage played a role in mediating the effect of strategic planning on company performance. Research limitations/implications: The research data set had collected using a questionnaire. After the data set had collected, an analysis had been finished using PLS Practical implications: Strategic planning can improve company performance through increased competitive advantage as an intervening variable. Originality/value: The paper is original. Paper type: The type of this research is causal research because the purpose of this study is to determine the effect of variables on other variables.